Penerapan Pemberdayaan Masyarakat Dalam upaya Pencegahan Kejadian Hipertensi di RT 004/RW 002 Kota Banjarbaru - Muhammad Rafly Fajar; Rudi Fakhriadi SKM., M.Kes (Epid); Bella Cornelia Anggut; Siti Habibah Maulydia; Wulandari - - (Universitas Lambung Mangkurat, 2022)
Hypertension is a risk factor for atherosclerosis, stroke, heart failure, and kidney failure (Nugraha, 2019). Currently hypertension is a degenerative disease experienced by the elderly, but currently hypertension can also be experienced by young people. The methodology used in this community service activity is visiting residents' homes one by one, then giving pre-test questions, checking blood pressure and providing education or counseling by presenting material on the definition of hypertension, risk factors, symptoms, forms of prevention and control and lastly conduct an evaluation of the counseling participants after the presentation of the material in the form of questions and answers about the material that has been presented to measure the residents' understanding and fill out the post-test. The results of counseling and empowerment carried out for RT residents. 004 RW. 002 is known to have increased in the good category. It is known that the percentage from 64% to 100% after receiving education.